Conditional Reduction of Adult Born Doublecortin-Positive Neurons Reversibly Impairs Selective Behaviors - Garrett, Lillian; Zhang, Jingzhong; Zimprich, Annemarie; Niedermeier, Kristina M.; Fuchs, Helmut; Gailus-Durner, Valerie; Hrabě de Angelis, Martin; Vogt Weisenhorn, Daniela; Wurst, Wolfgang; Hölter, Sabine M. (Frontiers in Behavioral Neuroscience, 2015)
Adult neurogenesis occurs in the adult mammalian subventricular zone (SVZ) along the walls of the lateral ventricles and the subgranular zone (SGZ) of the hippocampal dentate gyrus. While a burgeoning body of research implicates adult neurogenesis in olfactory bulb (OB) - and hippocampal-related behaviors, the precise function continues to elude. To further assess the behavioral importance of adult neurogenesis, we herein generated a novel inducible transgenic mouse model of adult neurogenesis reduction where mice with CreERT2 under doublecortin (DCX) promoter control were crossed with mice where diphtheria toxin A (DTA) was driven by the Rosa26 promoter. Activation of DTA, through the administration of tamoxifen (TAM), results in a specific reduction of DCX+ immature neurons in both the hippocampal dentate gyrus and OB. We show that the decrease of DCX+ cells causes impaired social discrimination ability in both young adult (from 3 months) and middle (from 10 months) aged mice. Furthermore, these animals showed an age-independent altered coping behavior in the Forced Swim Test without clear changes in anxiety-related behavior. Notably, these behavior changes were reversible on repopulating the neurogenic zones with DCX+ cells on cessation of the tamoxifen treatment, demonstrating the specificity of this effect. Overall, these results support the notion that adult neurogenesis plays a role in social memory and in stress coping but not necessarily in anxiety-related behavior.